Do Institutions Affect Social Preferences? Evidence from Divided Korea - Byung-Yeon Kim; Syngjoo Choi; Jungmin Lee; Sokbae Lee; Kyunghui Choi (Institute for the Study of Labor (IZA), 2013)
The Cold War division of Korea, regarded as a natural experiment in institutional change, provides a unique opportunity to examine whether institutions affect social preferences. We recruited North Korean refugees and South Korean students to conduct laboratory experiments eliciting social preferences, together with standard surveys measuring subjective attitudes toward political and economic institutions. Our experiments employ widely used dictator and trust games, with four possible group matches between North and South Koreans by informing them of the group identity of their anonymous partners. Experimental behavior and support for institutions differ substantially between and within groups. North Korean refugees prefer more egalitarian distribution in the dictator games than South Korean students, even after controlling for individual characteristics that could be correlated with social preferences; however, two groups show little difference in the trust game, once we control for more egalitarian behavior of North Koreans. North Korean refugees show less support for market economy and democracy than South Korean subjects. Attitudes toward institutions are more strongly associated with the experimental behaviors among South Korean subjects than among North Korean subjects.
Keywords: C92; C93; D03; P20; 330; social preferences; experiment; institutions; market economy; democracy